LONGITUDINAL STUDY OF THE IMPACT OF HEALTH CONFIDENCE ON INFLAMMATORY BOWEL DISEASE OUTCOMES AND HEALTHCARE UTILIZATION. (22nd January 2022) - Tse, Chung Sang; Melmed, Gil; Weng, Chien-Hsiang; Shah, Samir; Weaver, Alandra; Oliver, Brant; Elwyn, Glyn; Siegel, Corey; van Deen, Welmoed
Abstract: INTRODUCTION: A growing body of data from the primary care population demonstrates that health confidence (a patient's belief of their ability and agency to manage their disease and impact the disease course) is an important psychosocial factor associated with chronic disease outcomes (e.g., blood pressure and glycemic control) and emergency department [ED] visits.[1] Health confidence has also been shown to be associated with inflammatory bowel disease (IBD) symptomatic burden, general well-being, and healthcare utilization.[2] We aim to explore factors that influence health confidence and examine its impact on IBD disease outcome and healthcare utilization in a longitudinal, multi-institutional cohort of adults with IBD. METHODS: We surveyed adults (age >18) with IBD and their GI providers (verified IBD diagnosis phenotype) at 11 GI clinics across the U.S. as part of the Crohn's and Colitis Foundation's IBD Qorus Learning Health System. Included patients reported health confidence, disease activity, and healthcare utilization at baseline and on follow-up 6-12 months thereafter between 2018 and 2021. Health confidence was assessed using the validated Wasson's health confidence Likert scale from 0 ('not confident at all') to 10 ('very confident').[1] We identified patient characteristics associated with health confidence using the Kruskal-Wallis test. A Fisher's exact test was used to examine the associations between baseline low vs high health confidence (score <8 vs ≥8) and adverse IBD outcomes. P<.05 was considered statistically significant. RESULTS: Adults with IBD (n=327; 62% Crohn's disease, 35% ulcerative colitis; 47% in remission) had a median baseline health confidence score of 8 (IQR 7-10; Table 1). Patients with low health confidence (score <8; n=197, 60%) were more likely to have active IBD (p<.0001), use opioids (p=.0001), and have had an ED visit in the preceding 6 months (p=.04; Table 1). Notably, in the subsequent 6-12 months, patients with low baseline health confidence were more likely to have a CT scan (87% vs 13%, p=.03) and be on opioids (100% vs 0%, p=0.02) (Table 2). A higher proportion of patients with low baseline health confidence used steroids (91% vs 9%), had an ED visit (88% vs 11%), and were hospitalized (91% vs 9%) 6-12 months thereafter, though these differences did not reach statistical significance (Table 2). CONCLUSION: Symptomatically active disease and ED visits may undermine patients' confidence to manage their disease, which in turn increases the frequency of subsequent radiographic diagnostic testing. Opioid use was correlated with low health confidence both as a predictor and outcome in this cohort. REFERENCES: 1. Wasson, J. et al. Family practice management 21.5 (2014): 8-12. 2. Tse, C. S., et al. Gastroenterology 160.6 (2021): S-58.